Enhancing flexibility evaluation in AC/DC distribution systems for sustainable energy integration - Wang, Luyang; Zhao, Qianyu; Wang, Shouxiang; Jiang, Xingyue (Frontiers in Energy Research, 2024)
With the exacerbation of environmental issues and energy crisis, the integration of renewable energy resources on a large scale has led to a surge in demand for flexibility in distribution system. Therefore, establishing a comprehensive flexibility evaluation index system holds significant importance for the construction, promotion, and development of AC/DC distribution systems. This paper primarily focuses on the flexibility evaluation of AC/DC distribution systems and presents a proposed flexibility evaluation index system along with a comprehensive evaluation method based on the ANP-Entropy weighting model. The flexibility evaluation index system, comprising 18 key indexes, is constructed based on four essential dimensions: overall flexibility performance, flexible resources participation, operational performance, and economic performance. Subsequently, the ANP-Entropy weighting model is employed to carry out a comprehensive evaluation of flexibility of AC/DC distribution systems. To verify the effectiveness of the proposed evaluation method, a case study is conducted. Furthermore, the study investigates the impacts of controllable distributed generator (CDG) capacity, energy storage system (ESS) capacity, and voltage source converter (VSC) capacity on the flexibility of AC/DC distribution systems.